Role of Natural Compounds Modulating Heme Catabolic Pathway in Gut, Liver, Cardiovascular, and Brain Diseases - Jayanti, Sri; Vitek, Libor; Verde, Camilla Dalla; Llido, John Paul; Sukowati, Caecilia; Tiribelli, Claudio; Gazzin, Silvia (Biomolecules, 2024)
The crucial physiological process of heme breakdown yields biliverdin (BV) and bilirubin (BR) as byproducts. BV, BR, and the enzymes involved in their production (the "yellow players-YP") are increasingly documented as endogenous modulators of human health. Mildly elevated serum bilirubin concentration has been correlated with a reduced risk of multiple chronic pro-oxidant and pro-inflammatory diseases, especially in the elderly. BR and BV per se have been demonstrated to protect against neurodegenerative diseases, in which heme oxygenase (HMOX), the main enzyme in the production of pigments, is almost always altered. HMOX upregulation has been interpreted as a tentative defense against the ongoing pathologic mechanisms. With the demonstration that multiple cells possess YP, their propensity to be modulated, and their broad spectrum of activity on multiple signaling pathways, the YP have assumed the role of an adjustable system that can promote health in adults. Based on that, there is an ongoing effort to induce their activity as a therapeutic option, and natural compounds are an attractive alternative to the goal, possibly requiring only minimal changes in the life style. We review the most recent evidence of the potential of natural compounds in targeting the YP in the context of the most common pathologic condition of adult and elderly life.
Keywords: senioři; Liver; játra; nemoci mozku; Brain Diseases; podpora zdraví; Health Promotion; Adult; hem; Humans; Bilirubin; Heme Oxygenase (Decyclizing); hemová oxygenasa (decyklizující); biliverdin; bilirubin; Biliverdine; dospělí; Aged; Heme; lidé